Power Dialectics in Managing Libraries - Laugu, Nurdin (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2023)
This paper was aimed at investigating the dialectics of power in library management in Islamic universities. The research used critical theory to understand power relations and ideology in the social dynamics of libraries. The research adopted a constructivist qualitative approach to examine the unique social phenomena of professional practices in which the power of ideology has taken place among library actors in a hidden way. The data collection technique employed interviews and observations validated through triangulation of sources, techniques, and time. The analysis technique used Miles and Huberman's three stages: display, reduction, and data conclusion/verification. The research results illustrate three main findings, namely the dialectic of ideology in the interaction of library actors that can be seen in the contestation between pluralist and non-pluralist groups, both among library actors and in its implications for library collections. The second issue is the struggle between internal and external actors in the library. This issue includes relations between the library and other units or with other library institutions. Lastly is the contestation between libraries and other institutions, especially international relations, such as corners managed in libraries.